The variables of strategic regulatory response: a discriminant analysis - Joseph A. Raelin (Research in Corporate Social Performance and Policy: A Research Annual Vol. 6, 1984)
Research is undertaken to identify variables which might distinguish proactive from reactive regulatory strategies on the part of a sample of business firms engaged in industrial R&D. A discriminant analysis of the data reveals one function containing 17 factors which correctly classifies 95% of the cases in terms of their strategic regulatory response. The policy significance of each of the findings is discussed.
Keywords: G18; G38; L10; 330; Strategic regulatory response; Social regulations; Economic regulations; Product development; Industrial R&D